Tradisi Wuat Wai (Bekal Perjalanan) sebelum Melanjutkan Pendidikan di Manggarai, Nusa Tenggara Timur - Leonardus Agung Mandut; Syahrul Syahrul; Wahid Hasyim TRA Beni; Arifin Arifin (Ideas Publishing, 2021)
The purpose of this study was to determine the tradition of ‘wuat wai’ for children in Manggarai before attending education, and the benefits of implementing the tradition of ‘wuat wai’ in educational institution. The approach used in this study was qualitative. The research subjects using purposive sampling technique consisted of ‘Tua Adat’ (community leaders) and people in Manggarai. Research data were collected through interviews and documentation. The data of this study were analyzed using descriptive qualitative analysis techniques. This study shows threes findings, namely, first, the tradition of ‘wuat wai’ used as an event to support success in education in Manggarai. Second, the tradition ‘wuat wai’ is very useful for the education of children in Manggarai by providing travel provisions. Third, travel provisions provided are moral support (motivation) and financial support. Tujuan penelitian ini adalah untuk mengetahui tradisi wuat wai untuk anak di Desa Todo sebelum mengikuti pendidikan dan manfaat pelaksanaan tradisi wuat wai pada pendidikan. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif. Subjek penelitian dengan teknik purposive sampling terdiri atas tua adat (tokoh masyarakat) dan masyarakat di Desa Todo, Manggarai. Data penelitian dikumpulkan melalui wawancara dan dokumentasi. Data penelitian ini dianalisis menggunakan teknik analisis kualitatif deskriptif. Hasil penelitian menunjukan tiga hal, yaitu, pertama, tradisi wuat wai dijadikan sebagi ajang untuk mendukung keberhasilan dalam pendidikan di Manggarai. Kedua, tradisi wuat wai sangat bermanfaat sebagai bekal perjalanan untuk melanjutkan pendidikan. Ketiga, bekal perjalanan yang diberikan untuk anak adalah dukungan moral (motivasi) dan dukungan finansial.